How to study - Fry, Ronald W. (Franklin Lakes, NJ : Career Press, 1996)
Offers advice on creating a work environment, excelling in class, getting motivated, using the library, and doing on-line research.
Includes index.
Books for the Teen Age (NYPL).
School Library Journal.
Young Adult
Keywords: Study skills; Study skills